Patient-reported quality of life in patients with relapsed/refractory cutaneous T-cell lymphoma: Results from the randomised phase III ALCANZA study. (July 2020) - Dummer, Reinhard; Prince, Henry M.; Whittaker, Sean; Horwitz, Steven M.; Kim, Youn H.; Scarisbrick, Julia; Quaglino, Pietro; Zinzani, Pier Luigi; Wolter, Pascal; Eradat, Herbert; Pinter-Brown, Lauren; Sanches, Jose A.; et al.
Abstract: Background: Brentuximab vedotin was approved for adult patients with CD30-expressing cutaneous T-cell lymphoma treated with prior systemic therapy based on improved response rates and progression-free survival with brentuximab vedotin (1.8 mg/kg once every 3 weeks; ≤16 cycles) versus physician's choice (methotrexate/bexarotene; ≤48 weeks) in the phase III ALCANZA study. Quality of life (QoL) in ALCANZA patients was also examined. Methods: QoL measures in ALCANZA were based on the Skindex-29, Functional Assessment of Cancer Therapy-General (FACT-G) and European QoL 5-dimension (EQ-5D) questionnaires. Results: Mean maximum reduction from the baseline Skindex-29 symptom domain score (key secondary end-point) was greater with brentuximab vedotin than physician's choice (–27.96 versus –8.62); the difference, –18.9 (95% confidence interval –26.6, –11.2; adjusted p  < 0.001), exceeded the study-defined minimally important difference (9.0–12.3). Mean changes from baseline to end-of-treatment visit total FACT-G scores were similar with brentuximab vedotin and physician's choice (0.15 versus –2.29). EQ-5D changes were also comparable between arms. Among brentuximab vedotin-treated patients with peripheral neuropathy (PN), mean maximum reduction in Skindex-29 symptom domain was –35.54 versus –11.11 in patients without PN. PN had no meaningful effect on FACT-G and EQ-5D QoL scores. Conclusions: In summary, brentuximab vedotin produced superior reductions in symptom burden compared with physician's choice, without adversely impacting QoL. QoL was unaffected by the presence of PN in brentuximab vedotin-treated patients. Clinical trial registration: NCT01578499 . Highlights: Cutaneous T-cell lymphomas are incurable with a chronic course. Disfiguring and painful symptoms affect patients' quality of life. New treatments are needed to improve symptom burden and maintain quality of life. Brentuximab vedotin significantly reduces skin symptom burden. Treatment-emergent peripheral neuropathy had no impact on overall quality of life.